An Analysis of the PROMISE and ISBSG Software Engineering Data Repositories - Cheikhi, Laila; Abran, Alain (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
There exist two ongoing large repositories of software projects in the software engineering community: the repository of the International Software Benchmarking Standards Group (ISBSG) and the Repository referred to as PROMISE (PRedictOr Models In Software Engineering). Researchers interested in using the datasets have to conduct their own analysis of the datasets within these repositories that figure out what contents are suitable for their purposes. Repositories designed without users (researchers and Industrial) needs in mind greatly are more challenging to use. This paper present an analysis of both repositories and provide users with additional information on these datasets by identifying the topics addressed, highlighting their descriptiveness, and their availability, and by indicating whether or not further details are available in order to enhance their reusability in further empirical studies. Recommendations to both PROMISE managers and datasets owners are also suggested to improve the usefulness of the data provided.